The management of problem-solving : positive results from productive thinking - Tarr, Graham (London : Macmillan, 1973)
The book deals with problem solving in management. It stresses the way one thinks determines the result he gets, so for positive results, you need productive thinking.
Includes bibliographical references and index.
oif 29/01/2019
Loans
Keywords: Management; Problem solving